MENINGKATKAN KETERAMPILAN BERBICARA BAHASA ARAB DENGAN METODE MUHADATSAH MENGGUNAKAN MEDIA POCKET BOOK DI MA KHAS KEMPEK - Eis Nabillah; Septi Gumiandari (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2024)
Arabic speaking skills involve the ability to communicate orally in Arabic accurately, clearly and effectively. Arabic speaking skills include the ability to understand and use vocabulary, grammar and appropriate intonation in speaking. As happened at MA Khas Kempek to improve Arabic language skills. This research aims to determine (1) the application of the muhadatsah method in Arabic speaking skills at MA Khas Kempek (2) the application of pocket book media in Arabic speaking skills at MA Khas Kempek (3) the use of the muhadatsah method with pocket book media in improving speaking skills Arabic at MA Khas Kempek. This study uses a qualitative method. The data collection technique used in this research was interviews with 4 respondents. The research results revealed that (1) The application of pocket book media is used to make it easier for students to memorize and master Arabic vocabulary. The pocket book media used at MA Khas Kempek is in the form of an application that can be accessed on a cellphone or computer. (2) The use of the muhadatsah method with pocket book media in improving Arabic speaking skills really helps students, helps students so that students can speak Arabic with the correct structure and students can master Arabic vocabulary and memorize a lot of vocabulary as well.